Current knowledge about Chronic fatigue syndrome / myalgic encephalomyelitis (CFS/ME) causes - summary - Monika Prylińska-Jaśkowiak; Marcin Kożuchowski (Kazimierz Wielki University, 2022)
Chronic Fatigue Syndrome (CFE) is a severe and disabling disease whose etiology has not yet been elucidated. This implies the lack of a specific biomarker for the diagnosis of PE, and no causal treatment. There are a number of diagnostic criteria that facilitate the diagnosis of PE, but it is still a diagnosis with exclusion. This chapter reviews the scientific literature systematically, summarizing the available knowledge about the probable etiology of Chronic Fatigue Syndrome. The current topic of the influence of SARS-Cov-2 virus infection on the development of symptoms of IPC was also taken into account in particular. A clear explanation of the etiology of PE is necessary for the further development of scientific knowledge about the Chronic Fatigue Syndrome.